2024
DOI: 10.1021/acs.jchemed.4c00076
|View full text |Cite
|
Sign up to set email alerts
|

Mass Is Better than Light: Students’ Perception of Using Spectrophotometry and Gravimetric Analysis to Determine the Formula of a Hydrate in the General Chemistry Lab

Robert D. Milligan,
Donald J. Wink

Abstract: A key part of the practice of chemistry is the analysis of chemical composition, including through gravimetric analysis and spectrophotometry. However, the complexity of doing multiple calculations to obtain analytical evidence, such as that required to determine an empirical formula, presents a challenge if such analytical methods are to be understood by students and if they support meaningful learning about other chemical concepts and methods. In this study, we investigate student use of spectrophotometry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…Specifically, this tendency was observed in the absence of an intervention focused on the particulate level. Milligan and Wink (2024) also reported that students more readily used and learned via directly observable properties (e.g., mass) than with indirectly observable properties (e.g., absorbance) . In our findings, there were different ways of reasoning with color and we illustrate when this can be a limitation and when it can be an affordance.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Specifically, this tendency was observed in the absence of an intervention focused on the particulate level. Milligan and Wink (2024) also reported that students more readily used and learned via directly observable properties (e.g., mass) than with indirectly observable properties (e.g., absorbance) . In our findings, there were different ways of reasoning with color and we illustrate when this can be a limitation and when it can be an affordance.…”
Section: Discussionsupporting
confidence: 51%
“…These findings suggest that for molecular-level light–matter interaction phenomena, intentional support may be needed to develop students’ reasoning at the submicroscopic level . This finding is echoed in recent work comparing gravimetric methods to spectrophotometric methods . Milligan and Wink reported four perspectives of description from students’ written lab reports about using spectrophotometric methods.…”
Section: Literature Backgroundmentioning
confidence: 91%
See 2 more Smart Citations